Effectiveness of stretching and bracing for the treatment of osteoarthritis-associated joint contractures prior to joint replacement: a systematic review protocol - Vivian A Welch; T Mark Campbell; Bahareh Bahram Ghaedi; Elizabeth Tanjong Ghogomu; Marie Westby (BMJ Open)
Introduction Many patients with osteoarthritis (OA) develop restrictions in passive range of motion (ROM) of their affected joints (called contractures), leading to increased pain and reduced function. Effective treatment to reverse OA-associated contractures is lacking. Our aim is to evaluate the effectiveness of stretching and bracing on native (non-operated) joint contractures in people with radiographically diagnosed OA.Methods and analysis We will search the following databases without time restriction: Cochrane Library (CENTRAL, Database of Abstracts of Reviews of Effects, Health Technology Assessment Database), MEDLINE, Embase, CINAHL, SCI-EXPANDED (ISI Web of Knowledge) and PEDro. Other sources will include WHO International Clinical Trials Registry Platform, reference lists of included studies, relevant systematic reviews and textbooks. We will include randomised controlled trials (RCTs), controlled clinical trials, controlled before-and-after studies, cohort studies and case–control studies that include participants ≥18 years of age with radiographic evidence of OA. Participants with inflammatory arthropathies or those that have undergone joint arthroplasty will be excluded. Interventions will include therapist-administered or patient-administered stretching, use of an orthosis (static or dynamic), use of serial casting and/or adjunctive modalities. Outcomes will include joint ROM (active and passive), pain (rest and/or activity related), stiffness, activity limitations, participation restrictions, quality of life and adverse events. Studies will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Study inclusion, data extraction and quality assessment will be performed independently by two reviewers. Risk of bias will be assessed using appropriate tools for each study design. Data synthesis will be performed using Cochrane Review Manager software. If sufficient data are available, meta-analysis will be conducted. We will summarise the quality of evidence using Grading of Recommendations Assessment, and the effect size of interventions for RCT and non-RCT studies.Ethics and dissemination Ethics approval not required because individual patient data are not included. Findings will be disseminated in a peer-reviewed journal.PROSPERO registration number CRD42019127244